Threat to tropical oils - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The harvest of the first commercial crop of a genetically engineered oilseed plant took place last summer, in the south-east of America. The rapeseed plant had been altered by the biotechnology company Calgene of Davis, California, to produce...